Finding Blue Oceans in Tourism: Using Text Mining to Identify Business Opportunities in Tourism - Nogueira, Samira dos Santos (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research and CRM